Цифрове мовчання: право на збереження приватності у європейському електронному просторі - Кіріяк; Kiriiak, Оксана; Oksana (м. Харків: Право, 2024)
In the contemporary digital era, the notion of "digital silence" has emerged as a critical concept in discussions surrounding privacy, data protection, and online autonomy, particularly within the European Union (EU). This paper presents an in-depth analysis of the multifaceted phenomenon of digital silence, examining its definition, manifestations, legal implications, societal dynamics, and ethical considerations. Drawing upon extensive literature, case law, regulatory frameworks, and empirical research, this comprehensive study offers a nuanced understanding of digital silence and its significance in shaping the evolving landscape of digital rights and responsibilities in Europe. By exploring the intersections of law, society, and technology, this paper contributes to ongoing debates on digital privacy, data protection, and the ethical dimensions of digital behavior, offering insights for policymakers, legal scholars, technologists, and individuals navigating the complexities of the digital age.
Preserving Privacy: Exploring Digital Silence in the European Context
Keywords: human rights; digital silence; right to privacy; right to be forgotten; right to erasure; digital freedom